Frequency of oral lichen planus in patients with noninsulin dependent diabetes mellitus - Ahmed, Ijaz; Nasreen, Sarwat; Jehangir, Umer; Wahid, Zarnaz (Journal of Pakistan Association of Dermatologists, 2017)
Background The association between diabetes mellitus and lichen planus (LP), especially oral lichen planus, has been the subject of much research but the conclusion is controversial. The reported frequency of oral LP in diabetes mellitus varies from 1.6% to 85%. Â Objective To determine the frequency of oral lichen planus in patients with noninsulin dependent diabetes mellitus as compared with normal subjects.Â Â Patients and methods Freshly registered cases of noninsulin-dependent diabetes mellitus with suspected lesions of oral lichen planus, fulfilling the selection criteria, belonging to both sexes, aged 40-70 years were enrolled. After an informed consent, enrolled patients were examined following a detailed history and were subjected to biopsy and histopathology. Any relevant investigations were performed where required. An equal number of age- and sex-matched controls were also studied for oral LP.Â Â Â Â Â Â Â Results 86 patients comprising 49 (57%) females and 37 (43%) males, aged 40 to 70 years, mean age being 51.3 years, were studied in three age groups i.e. 40-50 years, 51-60 years and >60 years. Among these patients 8 (6.9%) had histopathologically confirmed oral lichen planus (P<0.05). Only 1 (1.2%) subject from the control group had the histopathologically confirmed disease. There were 5 females (62.5%) and 3 males (37.5%). Buccal mucosa was involved in 7 patients (87.5%). Â Conclusion Oral lichen planus has a significant association with noninsulin dependent diabetes mellitus as compared to normal population. Â